Horizontal mergers, firm heterogeneity, and R&D investments - Noriaki Matsushima; Yasuhiro Sato; Kazuhiro Yamamoto (Osaka University, Institute of Social and Economic Research (ISER), 2009)
We investigate the incentive and the welfare implications of a merger when heterogeneous oligopolists compete both in process R&D and on the product market. We examine how a merger affects the output, investment, and profits of firms, whether firms have merger incentives, and, if so, whether such mergers are desirable from the viewpoint of social welfare. We also derive equilibrium configurations and explore their welfare properties.
Keywords: L41; L13; O32; 330; mergers; oligopoly; R&D; heterogeneity